PERKEMBANGAN PRADEWASA DAN LAMA HIDUP IMAGO Psyttalia sp. (Hymenoptera: Braconidae), PARASITOID LARVA LALAT BUAH Bactrocera dorsalis HEND (Diptera: Tephritidae) - Pujiastuti, Yulia (Jurnal Rekayasa Lingkungan)
The objective of the research were to investigate level parasitization, immature development period, longevity of adult parasitoids, along with number of progeny and parasitoid sex of Psyttalia sp. attacking larvae of Bactrocera dorsalis. This experiment was conducted in Laboratory of Entomology, Department Plant Pest and Diseases Faculty of Agriculture, Sriwijaya University from March to September 2007. The result showed that the average level of parasitization of Psyttalia sp. reached 24.24%. The highest one was 30% and the lowest was 16.7%. The immature development period of Psyttalia sp. ranged from 24-31 days with average 27.5 days. Longevity of imago parasitoids which stored at 5 0C was 14.1 days. In the research, the progeny of parasitoids which produced was females with percentage of females reached 59.99% and percentage of males reached 39.99%.Keywords: fruit flies, Bactrocera dorsalis, parasitoid, Psyttalia sp.